Components of the Patient-Centered Medical Home Associated with Perceived Access to Primary Care - Schuttner, Linnaea (J Gen Intern Med, 2020)
BACKGROUND: Following implementation of the patient-centered medical home (PCMH) within the Department of Veterans Affairs (VA), access to primary care improved. However, understanding of how this occurred is lacking. OBJECTIVE: To examine the association between organizational aspects of the PCMH model and access-related initiatives with patient perception of access to urgent, same-day, and routine care within the VA. DESIGN: Cross-sectional PARTICIPANTS: Veterans who responded to the annual Survey of Healthcare Experiences of Patients in 2016 (N = 241,122 patients) and primary staff who responded to VA National Primary Care Provider and Staff Survey (N = 4815 staff). MAIN MEASURES: Three outcomes of perception of access: percentage of patients responding in the highest category for same-day care (waiting ≤ 1 day), urgent care (always receiving care when needed), and routine care (always receiving checkups when desired). Predictors were staff-level report of access-related initiatives and organizational factors in the clinic. We used generalized estimating equations to model associations, adjusting for characteristics of patients and their respective clinics. KEY RESULTS: Access was significantly better in clinics where staff reviewed performance reports (+ 0.9% in the highest perception of access for urgent care, P < 0.01; + 1.2% for routine care, P < 0.001), leadership was supportive of the PCMH (+ 1.6% for urgent care, P < 0.01), and initiatives to improve access included open access (+ 0.8% to + 1.7% across all outcomes, P < 0.01) and telehealth visits (+ 1.2% to + 1.4%, P < 0.001). Perceived access was worse in clinics with moderate staff burnout (− 1.1% to − 1.4%, P < 0.001), primary care provider turnover during the past year (− 1.0% to − 1.6%, P < 0.001), or medical support assistant turnover in the past year (− 0.9% to − 1.4%, P < 0.001). CONCLUSIONS: Perception of access was strongly associated with identifiable organizational factors and access-related initiatives within VA primary care clinics that could be adopted by other health systems. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11606-020-05668-7) contains supplementary material, which is available to authorized users.